2010
DOI: 10.3390/rs2081973
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing and Geospatial Technological Applications for Site-specific Management of Fruit and Nut Crops: A Review

Abstract: Site-specific crop management (SSCM) is one facet of precision agriculture which is helping increase production with minimal input. It has enhanced the cost-benefit scenario in crop production. Even though the SSCM is very widely used in row crop agriculture like corn, wheat, rice, soybean, etc. it has very little application in cash crops like fruit and nut. The main goal of this review paper was to conduct a comprehensive review of advanced technologies, including geospatial technologies, used in site-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 45 publications
(77 reference statements)
0
33
0
Order By: Relevance
“…Because the purpose of this research was to have a longterm management plan and to integrate wider range of data, all information can be correlated with each other or with other future data and statistics (Panda et al, 2010). Future focus and development will be mainly on system maintenance, including system enhancement and upgrading rather than to create a new system.…”
Section: Resultsmentioning
confidence: 99%
“…Because the purpose of this research was to have a longterm management plan and to integrate wider range of data, all information can be correlated with each other or with other future data and statistics (Panda et al, 2010). Future focus and development will be mainly on system maintenance, including system enhancement and upgrading rather than to create a new system.…”
Section: Resultsmentioning
confidence: 99%
“…Peña-Barragan et al [36] showed that multispectral imagery is suitable to discriminate cover crops from olive trees and to estimate olive tree surface with good accuracy (92%). Panda et al [37] reviewed several techniques used in fruit and nut crop management and described the methods used to differentiate orchards from other land uses, and how GIS and models can then be applied for analyses. No accurate discrimination of tree crop types has been achieved without a significant input of field knowledge.…”
Section: Tree Crop Planting Patternmentioning
confidence: 99%
“…In recent years, horticulture development is emerging as one of the major thrust area in agriculture sector in the developing countries [1]. For optimum utilization of available land resource, delineation of orchards(or horticulture in general) and spatial analysis using remote sensing can provide useful information for management and decision making for successful application of site-specific crop management, quantification and scheduling of precise and proper fertilizer, irrigation needs, application of pesticides for pest and disease management and has potential for increasing net returns and optimizing resource [2]. One of the key components of precision agriculture is data collection.…”
Section: Introductionmentioning
confidence: 99%